Morphea in Middle Anatolia, Turkey: a 5-year single-center experience - Bulur, Isil; Erdoğan, Hilal Kaya; Karapınar, Tekden; Saracoglu, Zeynep Nurhan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Morphea, also referred to as localized scleroderma, is a rare fibrosing skin disorder of undetermined cause. Aim: We report our single-center experience with morphea. Material and methods: The study included 53 patients who were diagnosed with morphea by histopathology in our department between 2010 and 2015. Study data were collected retrospectively from the records of morphea patients. Results: The study included 53 patients (38 women, 15 men), and median age at onset was 39.0 (range: 8–85) years. Thirty (56.6%) patients had circumscribed morphea, 15 (28.3%) had generalized morphea, and 7 (13.2%) had linear morphea. One patient had mixed variant morphea (generalized, pansclerotic and linear morphea). ANA positivity was detected in 12 (22.6%) patients, but analysis for an association between the presence of ANA and morphea types, patients’ characteristics did not reveal any significant associations. We did not observe any extracutaneous manifestations in patients during follow-up period. There were 2 of 53 patients who had concomitant autoimmune disorder including vitiligo and spondyloarthritis. Thirty (56.6%) patients received only topical treatment. The patients with clinical improvement who were treated with systemic therapy received methotrexate (26.4%), colchicine (9.4%), mycophenolate mofetil (5.7%) and prednisolone (1.9%). Conclusions: Our results related to the demographic data of the patients and morphea types were consistent with the literature. On the other hand we observed that methotrexate was mostly used as an effective treatment option for generalized morphea.